'New' but 'Squeezed': Middle Class and Mortgaged Homeownership in Croatia. (December 2022) - Mikuš, Marek
Some recent anthropological accounts of middle classes centred on their indebted home-ownership. They stressed its two contrastive logics fitting a wider binary – exposing 'squeezed' middle classes in the global North to increasing risks, and supporting the ascent of their 'new' counterparts in the South. The genealogy of middle-class housing debt in Croatia presented in this article reveals another, post-socialist trajectory where mundane and opaque institutional practices regulating access to housing finance, such as bank credit scoring and the allocation of state housing benefits, were key in steering a middle class inherited from socialism towards mortgaged home-ownership. The latter was articulated as a middle-class experience only after the 2000s credit boom had come to an end and the consequences of rampant predatory lending became visible and subject to contestation. The resulting middle-class subjectivities are ambiguous and, as comparisons with other Eastern European cases suggest, accessible for a range of political projects.